Agile Implementation for Inventory (Case study: Business Unit of Private University) - Swastyastu, Cempaka Ananggadipa; Shanty, Ratna Nur Tiara; Sari, Rika Puspita; Wikanningrum, Anggit (Journal of Information Technology and Cyber Security, 2024)
The Unitomo Employee and Lecturer Business unit in the city of Surabaya, Indonesia, has several problems arising from the implementation of a manual system in the form of a paper-based system, which has the potential risks, such as 1) Damage and Risk of data loss, 2) Ineffectiveness in making reports; 3) Increased risk of human error caused by transaction volume, lack of management, and non-integration data; 4) Limited user accesses to the ledger, Time-consuming processes, and no collaboration. This research aims to overcome this problem by developing an inventory recording system using an Agile approach with the Scrum framework, PHP with the Slim 3 framework, MySQL, black box testing, and adding revenue and sales features as a difference from previous research. The research results show that the system developed was successful in helping Unitomo Business unit employees and lecturers overcome their problems, especially in monitoring the amount of inventory stock. The proposed system has features for recording incoming and outgoing goods transactions and sales and income reports. The use of the Agile Scrum method in software development helps teams in project planning and monitoring progress throughout the design process.